IDENTIFIKASI KONDISI SOSIAL EKONOMI PENDUDUK DI KELURAHAN KELAYAN LUAR KECAMATAN BANJARMASIN TENGAH - Lisa Febrina; Ellyn Normelani; Karunia Puji Hastuti (JPG (Jurnal Pendidikan Geografi), 2016)
This study entitled "Identification of the Socio-Economic Conditions of Residents in the Village kelayan Outer Central District of Banjarmasin. The purpose of this study was to determine the socioeconomic identification of the population in Sub kelayan Outer Central District of Banjarmasin.The population in this study is the head of the family in the Village kelayan Outer Central District of Banjarmasin with sample number 269. The primary data obtained through field observation and questionnaires, while secondary data obtained from the Village kelayan Affairs, District Central Banjarmasin, and journals associated with the research. The analysis technique used is the technique of percentage. Results of this research that socio-economic conditions of low it is because of work income is minimal so that the head of the family need to survive is to improve the social and economic condition such as looking for a second job, judging from the social conditions that family education is in the complaints kelayan Affairs low levels of education. The results of the socio-economic growth quite well in the village kelayan Affairs, This indicates that the level of welfare of the population is also high. Socio-economic growth is indicative of the success of the development. Keywords: Identification, Social Economy, Population